Zapiski 1980-1984 - Popieluszko, Jerzy, 1947-1984. (Paris : Editions Spotkania, 1985)
Autobiography of the Polish priest.
Keywords: Popieluszko, Jerzy, -- 1947-1984.; Catholic Church -- Poland -- Clergy -- Biography